IMPLEMENTASI FUZZY MAMDANI PADA PENDISTRIBUSIAN BERAS MISKIN - Husniati -; Nurmaliana Pohan (RJOCS (Riau Journal of Computer Science), 2017)
One of the government's efforts in improving the basic needs for the poor, the government has developed the distribution of rice for the poor (Raskin). Poor distribution of subsidized rice for the poor, aiming to reduce the burden of expenditure of poor households. Besides, this program is intended to improve access of the poor in meeting basic needs as one of the basic rights of the people. This is one program both central and local government. In the area of research to date Raskin still poses some problems, one of them is not well targeted distribution, making it less useful for the recipient. In this study, to help the village Kotabaru Reteh to determine the feasibility of Raskin recipients is to input data of family and the value of the criteria set by the government Subdistrict Keritang as benchmarks Raskin recipients, then based on the variable input that the system can calculate the degree of poverty of a family based on fuzzy membership function mamdani. From the calculation results, it can be mapped feasibility of a family in accepting the rice for the poor so they would not be no cheating in the distribution of Raskin.